Investigação de anticorpos para Neospora caninum em humanos e sua relação com a infecção pelo Vírus da Imudeficiência Humana - Cunha, Cíntia Lidiane Guidotti Aguiar (2013)
Neospora caninum is an obligate intracellular protozoan, causes neosporosis and resembles formation by Toxoplasma gondii tissue cysts in their hosts. Humans are not considered intermediate hosts for N. caninum, but its zoonotic potential is questionable, because of the close phylogenetic relationship with T. gondii and the report of a study, which fetuses of nonhuman primates, Rhesus, (Macaca mulatta) infected artificially with lesions similar to those caused by congenital toxoplasmosis. The present study aimed to verify the occurrence of antibodies to N. caninum in humans and its possible association with HIV infection and other risk factors. The presence of antibodies to N. caninum was determined from a sample of 156 HIV-positive patients and 100 HIV-negative individuals of Pelotas, Rio Grande do Sul, Brazil, through the reaction of Indirect Immunofluorescence Assay (IFA), with initial dilution of 1:25. Antibody titers found by IFA ranged between 25 and 800. Samples of 256 human sera analyzed, 47 (18.3%) were positive for N. caninum. Since antibodies to this protozoan were found in 36 HIV-positive patients (23.1%) and in 11 HIV-negative individuals (11%). Multivariate analysis showed that HIV-positive patients who have CD4+ T-lymphocyte count ≤ 350 cells/mm3 have 2.4 times more likely to be seropositive for N. caninum. HIV-negative individuals who have seropositivity for T. gondii have 4.71 times more likely to have antibodies to the agent studied. The results indicate the exposure of humans to N. caninum, with higher prevalence in immunocompromised individuals.